The Impact of Environmental Certification on Hotel Performance Ranking - Sara BORGES; Jorge ALVES; Nuno MOUTINHO (Communications of International Proceedings, 2023)
The importance attached by companies to the environment has been growing, due to increasing pressure from the population. Also, in tourism industry there has been an increased concern for environmental issues, and the hotel companies are working to improve their environmental responsibility through the requirements that environmental certification entails. However, it is not known whether the impact of this decision contributes to an improvement in the performance of these companies. The aim of this study is to find whether hotel companies with environmental certification are better positioned in the financial performance ranking. Based on a TOBIT estimation of the performance ranking of Portuguese hotel companies, calculated using the TOPSIS methodology, it is possible to conclude that the characteristics of the hotel industry influence financial performance. In particular, this study show that environmental certification positively affects the performance ranking of companies, so that companies with environmental certifications are better positioned in the financial performance ranking. The result seems to evidence that companies with environmental friendly hotels have higher performance, which may be related to the fact that consumers are willing to prefer these hotels over others.
Keywords: Environment; Environmental certification; Ranking performance; TOPSIS; TOBIT